Pengelolaan Keuangan Pedagang Ikan di Tempat Pelelangan Ikan Lumpur - Hikmatus Shobri Nafi’ah; Anita Handayani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This reasearch discuss the financial management of fish traders at the Fish Auction Place in Lumpur. The aim of this study is to analyze the financial management practices applied by fish traders, as well as the factors that influence the efficiency of their financial management. The reasearch method used is descriptive qualitative, collecting data trough in-depth interviews telated to financial management. The result show that fish traders generally manage their finances traditionally whithout formal records. They face challenges such as income fluctuations and lack of planning. Some traders adopt conservative strategies by avoiding debt and saving. This study indicates that financial management training is not necessary, as the traders have successfully accumulated significant assets despite lacking adequate financial knowledge.